2020
DOI: 10.1080/20961790.2020.1795377
|View full text |Cite
|
Sign up to set email alerts
|

Forensic isoscapes based on intra-individual temporal variation of δ18O and 206Pb/207Pb in human teeth

Abstract: Isotopic signatures used in the georeferencing of human remains are largely fixed by spatially distinct geologic and environmental processes. However, location-dependent temporal changes in these isotope ratios should also be considered when determining an individual's provenance and/or trajectory. Distributions of the relevant isotopes can be impacted by predictable external factors such as climate change, delocalisation of food and water sources and changes in sources and uses of metals. Using Multi-Collecto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 50 publications
(117 reference statements)
0
4
0
Order By: Relevance
“…Because there are relatively few databases of isotope test results for modern human bone and teeth, isoscapes based on human tissues are unavailable for most world regions. One notable exception is the publication of Pb and O tooth enamel isoscapes for the continental U.S. (Keller et al, 2016; Regan et al, 2021). There are some additional tissue isotope reference data sets available; they are discussed in Section 3.…”
Section: Stable Isotopes In Humansmentioning
confidence: 99%
See 2 more Smart Citations
“…Because there are relatively few databases of isotope test results for modern human bone and teeth, isoscapes based on human tissues are unavailable for most world regions. One notable exception is the publication of Pb and O tooth enamel isoscapes for the continental U.S. (Keller et al, 2016; Regan et al, 2021). There are some additional tissue isotope reference data sets available; they are discussed in Section 3.…”
Section: Stable Isotopes In Humansmentioning
confidence: 99%
“…Finally, some studies have found lead isotope ratios to be potentially useful for geolocation and thus human identification (Kamenov & Curtis, 2017; Keller et al, 2016; Regan et al, 2021). Similar to Sr, Pb can substitute for calcium in bone and teeth.…”
Section: Stable Isotopes In Humansmentioning
confidence: 99%
See 1 more Smart Citation
“…note that the error bars are smaller than the size of the symbols. The isotopic range of the limited Pb isotope data of German tooth enamel (n = 6) and hair samples (n = 13) from our unpublished data lie on the main data array with 206 Pb/ 207 Pb between 1.147 and 1.172. additional Us Pb isotope data from air Force cadets can be found in regan et al[39].…”
mentioning
confidence: 99%